Sepsis risk calculator versus risk-based approach for antibiotics initiation in neonates at risk of early onset sepsis: a randomized controlled trial from Indian tertiary center - Gowda, Preethi; Anand, Pratima; Debata, Pradeep; Yadav, Anita (International Journal Of Community Medicine And Public Health, 2025)
Background: Early onset sepsis (EOS) continues to have high morbidity and mortality with an estimated incidence of 0.3 to 0.8 per 1000 live births at >34 weeks’ gestation in high resource countries. The incidence in low resource countries is higher (2.2% of all live births from DeNIS study in India). Diagnosing EOS remains a significant clinical challenge and multivariate prediction models (sepsis calculators) can help optimize the management and use of antibiotics. Methods: Objective was to determine the proportion of neonates receiving antibiotics in two groups using Kaiser Permanente sepsis risk calculator (KPSRC) and Center for Disease Control (CDC) risk-based approach in neonates greater than 34 weeks’ gestation, at risk of EOS. This open labelled randomized controlled trial from tertiary care center in India evaluated the proportion of neonates who were recommended antibiotics in the two group, incidence of clinical or culture positive early onset sepsis, death within 72 hours of age and agreement (kappa value) between two groups. Results: Total 216 neonates at risk for EOS were enrolled to two groups by randomization to either CDC or KPSRC in a 1:1 ratio. Mean (SD) gestation and mean (SD) birth weight of enrolled neonates was 37.85±2.04 weeks and 2506.9±522.87 g respectively. KP calculator identified 5.56% neonates as eligible for antibiotics administration versus 19.44% by risk-based approach (p=0.02). Among those who did not receive antibiotics 1 neonate in KP group (0.98%) and 2 from CDC risk-based group (2.30%) (p=0.59) developed clinical sepsis and none developed culture positive sepsis. There was one death within 72 hours in KP group versus none in risk-based group (p=1.0). The agreement (kappa value) between KP calculator and risk-based approach to initiate antibiotics was 0.83. Conclusions: In neonates more than 34 weeks of gestation, antibiotics use was 28.6% less using KP calculator compared to risk-based approach, without increase in culture positive sepsis or neonatal death within 72 hours of life.